2007
DOI: 10.1007/s10669-007-9001-3
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and chemical speciation for the determination of Cu, Zn, Ni, Pb and Cd from refuse dump soils using the optimized BCR sequential extraction procedure

Abstract: The optimized BCR sequential extraction procedure (proposed by the Standards, Measurements and Testing Programme (SM&T) of the European Union) was applied to seven topsoil samples from refuse dump sites for the determination of Cu, Zn, Ni, Pb and Cd. The metals were partitioned into four operationally defined chemical fractions: acid extractable, reducible, oxidizable and residual, and analysed using flame atomic absorption spectrophotometry, FAAS.The results were compared with total metal concentrations obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
(23 reference statements)
5
14
0
2
Order By: Relevance
“…Sequential extraction was performed using a three-stage modified procedure recommended by BCR, which has been used for several studies [20].The elements chemical speciation were divided into four types: acid-extractable state, reducible state, oxidizable state, and residual state (Table 1). Subsequently, the concentrations of Zn, Pb, Cr, Cu, Ni, Cd, V, and Co were determined by using an inductively coupled plasma-optical emission spectrometer (ICP-OES).…”
Section: Experimental Analysismentioning
confidence: 99%
“…Sequential extraction was performed using a three-stage modified procedure recommended by BCR, which has been used for several studies [20].The elements chemical speciation were divided into four types: acid-extractable state, reducible state, oxidizable state, and residual state (Table 1). Subsequently, the concentrations of Zn, Pb, Cr, Cu, Ni, Cd, V, and Co were determined by using an inductively coupled plasma-optical emission spectrometer (ICP-OES).…”
Section: Experimental Analysismentioning
confidence: 99%
“…The results of the partitioning study reported by Umoren et al (2007) showed that zinc prevailed in the more soluble fractions and was distributed between the acid-extractable (32.4 %) and the reducible (40.3 %) fractions, whereas Pb was distributed mainly in the reducible fraction. Copper was predominantly associated with the reducible and residual fractions.…”
Section: Introductionmentioning
confidence: 96%
“…Staszewski et al (2012) present results of screening analysis of 23 Polish national parks contamination with Cu, Pb, Zn and Cd (metal concentration in needles of trees and metal concentrations in soils). The mobility of trace metals in soil, determined by solid-solution partitioning, could be assessed by a sequential leaching procedure or by single chemical extraction (Tessier et al 1979;Quevauviller et al1994;Umoren et al 2007;Rao et al 2008;Anju and Banerjee 2011;Peters 1999). Among the studied metals, Pb has no essential biological function, but is taken up by plants from metal-enriched soils.…”
Section: Introductionmentioning
confidence: 99%
“…The BCR procedure is commonly applied for more accurate estimation of the occurrence of metals in soil and it is recommended for the investigation of their migration from the soil to plants (Rauret et al, 2000;Sutherland and Tack, 2003;Wang et al, 2002;Pueyo et al, 2003;Umoren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%